In search of the "folk character" we would like to hear the dichotomy between folk, the profession, and scholarship - Kovačič, Mojca (Traditiones (Ljubljana), 2012)
Public Fund of the Republic of Slovenia for Cultural Activities (JSKD) is the main actor of the current cultural policy in the field of folklore activities in Slovenia. Guidelines of reinterpretation of dance and music traditions are formed by amateurs dealing with folklore, as well as scholars are invited to participate. After the historical review of the cultural policy in Slovenia, the article, based on interviews with performers of musical tradition, reveals the adjustments that musicians are making for the performances organized and supervised by JSKD. It also shows their attitude towards the given guidelines and reveals how much the competitiveness or actual desire for 'authentic' interpretation of folk music heritage influence such adjustments.
Keywords: ethnomusicology; Etnomuzikologija; folk music; Ljudska glasba; Ljudski glasbeniki; Folkloristika; folkloristics